STUDI FAKTOR PENYEBAB TINGKAT STRES PADA PASIEN GAGAL GINJAL KRONIS YANG MENJALANI HEMODIALISIS DI RUMAH SAKIT GAMBIRAN KEDIRI - Yoyok Yulianto; Nurwijayanti (STIKes Maharani Malang, 2022)
Introduction: Chronic non-communicable diseases such as cardiovascular disease, hypertension, diabetes mellitus, and chronic kidney disease, have replaced infectious diseases as a major public health problem.. The purpose of this study was to explore the study of factors that cause stress levels in chronic kidney failure patients undergoing hemodialysis at Gambiran Hospital, Kediri. Method: This study used an Qualitative case study approach that describes and explores the study of factors that cause stress levels in chronic kidney failure patients undergoing hemodialysis at Gambiran Hospital, Kediri. The sampling technique was purposive sampling, with inclusion and exclusion criteria. The researcher uses the credibility test to test the validity of the data. Result and analysis: The results of the thematic analysis, obtained four major themes, namely diet of patients with chronic kidney failure undergoing hemodialysis, family support for patients undergoing hemodialysis, hemodialysis services for patients with chronic kidney failure undergoing hemodialysis, and Genetics of patients with chronic kidney failure undergoing hemodialysis at Gambiran Hospital, Kediri. Discussion: The diet of patients with chronic kidney failure undergoing hemodialysis at Gambiran Hospital Kediri has decreased, family support for patients undergoing hemodialysis has received good support from their families, hemodialysis services for patients with chronic kidney failure undergoing hemodialysis are very good, families of patients with kidney failure are very good, suffering from diabetes and high blood Keyword: Stress, Chronic Kidney Failure, Hemodialysis